Resource Allocation on Low-Earth Orbit Edge Infrastructure: Taxonomy, Survey, and Research Challenges - Fabio Diniz Rossi; Paulo Silas Severo de Souza; Marcelo Caggiani Luizelli (IEEE Access)
Low Earth Orbit (LEO) Edge Computing integrates space technology with Edge Computing to enhance connectivity and reduce latency, addressing critical limitations of terrestrial infrastructures. By leveraging LEO satellites, this paradigm enables global, low-latency data processing for applications such as remote sensing, Earth observation, and worldwide communications. However, it also presents challenges in resource allocation, thermal management, and space debris mitigation. This paper provides a comprehensive taxonomy and in-depth survey on resource allocation strategies in LEO Edge environments, identifying key challenges and future research directions.